Security framework for low latency vanet applications - Wagan, A.A. (Institute of Electrical and Electronics Engineers Inc., 2014)
Vehicular Ad hoc Network (VANET) is a communication network for vehicles on the highway. Presently, VANET technology is surrounded with security challenges and it is essentially important for VANET to successfully implement a security measure according to the safety applications requirements. Many academia researcher have suggested a various solutions to encounter security attacks and also proposed models to strengthen security characteristics. The current most suitable security scheme for VANET is an Elliptic Curve Digital Signature Algorithm (ECDSA). However ECDSA is associated with high computational cost, therefore it is considered an inappropriate approach for low latency safety applications. In this study, a security framework is proposed to solve above issues; a proposed framework utilizes both traditional cryptographic schemes; asymmetric PKI and symmetric respectively. The asymmetric cryptography scheme is used to securely exchange the key and authentication process and symmetric cryptography scheme is used for low latency safety application (especially time critical safety applications). The suggested framework is not only reduce the latency but also enhance the security cryptography characteristics by establishing trust between ongoing vehicles. Â© 2014 IEEE.